Tourism Development Strategy for East Lombok Kesik Village in Economic Recovery Efforts: Tourism Development Strategy for East Lombok Kesik Village in Economic Recovery Efforts - Emi Yulia Hasanah; Prayitno Basuki; Adhitya Bagus Singandaru (Experimental Student Experiences, 2023)
The purpose of this study was to determine the tourism development strategy for Kesik Village, East Lombok, in an effort to restore the economy. This study uses a qualitative descriptive approach by collecting data through results of interviews with informants and documentation from the village of Kesik. Based on the results of this research, it can be concluded that from a cultural point of view, Kesik Village is a cultural tourism, because it has several cultural icons that other villages do not have. Kesik Village continues to improve in developing every potential that exists, both infrastructure and tourism potential that it has. Kesik Village desire to build a national standard swimming pool was triggered by its enthusiasm to contribute even more to the region and be able to increase local revenue, especially for coaching youth and athletes as well, as well as the hope that later the pool can become a place of competition at both the district level, Province to National. The development of Tirta Ratu Tourism has not been able to realize the tourism conditions it is proud of, due to various unresolved inhibiting factors such as inadequate quality of supporting facilities and result of the Covid-19 outbreak.